A distinctive, low‐grade oncocytic fumarate hydratase‐deficient renal cell carcinoma, morphologically reminiscent of succinate dehydrogenase‐deficient renal cell carcinoma. Issue 1 (12th April 2017) - Smith, Steven C; Sirohi, Deepika; Ohe, Chisato; McHugh, Jonathan B; Hornick, Jason L; Kalariya, Jigna; Karia, Sushil; Snape, Katie; Hodgson, Shirley V; Cani, Andi K; Hovelson, Daniel; Luthringer, Daniel J; et al.
Abstract : Aims: Fumarate hydratase (FH)‐deficient renal cell carcinoma (RCC) is a high‐grade, aggressive tubulopapillary carcinoma, arising predominantly in the setting of the hereditary leiomyomatosis–RCC syndrome of familial uterocutaneous leiomyomatosis and deficiency of FH. In contrast, succinate dehydrogenase (SDH)‐deficient RCC is a lower‐grade oncocytic carcinoma with cytoplasmic flocculence/vacuolation and inclusions, arising mostly in individuals harbouring germline mutations of subunit B of the SDH complex (SDHB). Herein we aim to report the clinicopathologic features of a novel form of FH‐deficient RCC showing a low grade oncocytic morphology, reminiscent of SDH‐deficient RCC. Methods and results: These distinctive, low‐grade oncocytic neoplasms, with solid, nested and focally tubular architecture (2–90 mm), arose in four males (aged 11–41 years). Uniform cytology of polygonal cells, with flocculent, vacuolated eosinophilic cytoplasm with scattered inclusions, fine chromatin, and inconspicuous nucleoli, was apparent. Despite these features suggestive of SDH‐deficient RCC, each tumour was confirmed as an FH‐deficient carcinoma with retained SDHB expression. One case showed a synchronous, anatomically separate, typical high‐grade FH‐deficient RCC; one other showed such a tumour at nephrectomy 4 years later. No progression has been noted at 3 and 7 years in the cases with only the SDH‐like lesions; the two cases with separate, typical FH‐deficient RCCs progressed. Conclusions: In summary, we characterize a novel oncocytic type of FH‐deficient RCC with a striking resemblance to SDH‐deficient RCC, posing a diagnostic challenge and raising concerns about sampling and multifocality for syndrome‐associated cases under surveillance protocols.